RELEVANSI PEMIKIRAN ULAMA BUGIS DAN NILAI BUDAYA BUGIS (Kajian tentang ‘iddah dalam Tafsir Berbahasa Bugis Karya MUI Sulsel) - Yusuf, Muhammad (Analisis: Jurnal Studi Keislaman, 2013)
This article temps to investigate Muslims Scholars of Bugis’ viewpoints base on the Qur’an in Tafesere Akorang Mabbasa Ogi by MUI of South  Sulawesi  when they ellaborated  verses of the Quran on ‘iddah and its relevance to the value of local wisdom and culture of the Bugis. The coherence of their viewpoints  and the  values  of local wisdom  and culture  of the  Bugis  has been ellaborated,  they  studied  verses of the  Quran about  ‘iddah are relevant or related. The Bugis people have princpile and philosophy of life which are related to the doctrine of Islam. They can stand on the values of local culture, not only because of undertanding Islam well, but also because of their consistence to the philosophy of life. ‘Iddah which have arranged time limit s\ala>s\ah quru>’ is not so difficult to be conducted by devorced women of Bugis. They are also able to protect  themselves  for not doing unproper thing (ih}da>d),  including  proper  marriageable.  The  devorced  women have  no  problem  and  difficulty  during  the  limitation   of  time (iddah and ih}da>d) to not marry for the time being, and they can protect  themselves  because  they  hand the  principle  and values of siri’, lempu’, asitinajang, and paccing. These principles which become values of purity and self honor.